DESAIN DAN IMPLEMENTASI SISTEM INFORMASI JUAL BELI RUMAH PADA PT. ADHIASTA KARYA PRATAMA - Suryani, Desy; Sari, Adika May; Rafik, Ahmad; Yani, Desri; Rosmita, Rosmita (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
In today's civilization, the delivery of information is very fast, with technology and internet speed getting faster from year to year. Therefore, all forms of information, especially in marketing products, are very quickly accessible to consumers using online media. PT. Adiastha Karya Pratama really needs an online marketing system that supports marketing its products by using a personal website, in this way consumers will be helped to find information that supports their interest in buying PT products. Adiastha Karya Pratama. At this time PT. Adiastha Karya Pratama operates in the housing developer sector. A web-based home sales information system has advantages, including being effective and efficient for buyers. Buyers only need to access the computer to search for house sales information. Has a function to track the location where the buyer will go to the location of the house for sale.